2010
DOI: 10.1007/s00431-010-1344-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidelines: what they are, why we need them and how they should be developed through rigorous evaluation

Abstract: The number of available clinical practice guidelines has grown enormously in the recent years, therefore requiring a correct approach and use of them. We present a revision of what guidelines are and serve, how to correctly develop and find them, and how to develop and evaluate them through rigorous scientific methods. Limits and benefits of guidelines are also discussed. An overview about the use of paediatrics' guidelines is finally reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The development of guidelines is a complex task that requires multidisciplinary members such as clinicians, methodological experts, policy makers and patient representatives . Studies have shown that the balance of disciplines within a guideline‐development group has considerable influence on the guideline recommendations, and panels dominated by single groups without diversification can result in intellectually and financially biased guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…The development of guidelines is a complex task that requires multidisciplinary members such as clinicians, methodological experts, policy makers and patient representatives . Studies have shown that the balance of disciplines within a guideline‐development group has considerable influence on the guideline recommendations, and panels dominated by single groups without diversification can result in intellectually and financially biased guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines, and their underpinning evidence, vary in quality and have been criticised for oversimplifying the complexity of primary care, where undifferentiated symptoms are commonplace and are associated with both minor illness and serious disease. 86,87 However, they do provide a standard of care, to improve service delivery and health outcomes against which to evaluate clinician action. 88 Comparison with existing literature Two randomised controlled trials have investigated DA testing and were not included in this review as they were not investigations for cancer: MRI for knee symptoms (the DAMASK trial) and hysterosalpingography (HSG) for infertility (the OATS trial).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Evidence‐based clinical guidelines, for which a rising interest can be noticed, may well prove the best instrument to link the macro and micro level. These guidelines are developed, often by medical professionals associations, as a tool to inform clinicians about the current state of knowledge regarding the benefits and limitations of specific technologies for defined health problems . The increasing complexity of health technologies, a growing desire to increase quality of care and reduce variation, and the necessity to control costs, has led to the growing use of clinical guidelines in the last 3 decades .…”
Section: Discussionmentioning
confidence: 99%